ASSESSMENT OF STAFF POTENTIAL IN THE FIELD OF SCIENTIFIC RESEARCH AT THE UNIVERSITY: CURRENT STATE AND DEVELOPMENT PROSPECTS - Хамзина, Ж.; Килыбаев, Т.; Сафронова, Людмила (Pedagogy and Psychology, 2022)
A project group of professors-researchers and postdoctoral students of the Kazakh National Pedagogical University named after Abai conducted a pilot sociological study of the state and prospects for the development of scientific activities of the teaching staff of the university. As a result of a test survey among the teaching staff of the university in the period from September 27 to October 2, 2021, the main advantages and the most problematic aspects of scientific research at the university were identified in terms of the personnel potential of science of Abay KazNPU, the quality and quantity of research projects and difficulties with scientific publications in journals from the Scopus / WoS, etc. The conclusions and conclusions obtained by the research team made it possible to recommend a number of measures to increase research activity, as well as specific measures due to the industry affiliation of the university. This article presents the first part of the study, concerning the quality of the human resources potential of the university.